1976
DOI: 10.2134/agronj1976.00021962006800060017x
|View full text |Cite
|
Sign up to set email alerts
|

Biological Significance of Reed Canarygrass Alkaloids and Associated Palatability Variation to Grazing Sheep and Cattle1

Abstract: Total basic alkaloid concentration of reed canarygrass (Phalaris arundinacea L.) is negatively correlated with palatability (selection when a choice is offered) of the grass to ruminant animals. The significance of these alkaloids to ruminants not offered a choice of pasture forage remained unknown. Our objectives were to determine whether alkaloid concentration and alkaloid type differences among reed canarygrass genotypes affect animal performance, grass intake, and health of grazing sheep and cattle. Replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 11 publications
2
34
0
Order By: Relevance
“…Total indole alkaloid concentration (gramine, tryptamines and carbolines) was inversely correlated with weight gains in lambs and steers (Marten et al 1976). Marten et al (1981) indicated that a total alkaloid concentration greater than 2.0 mg/g dry weight of forage reduces animal gains.…”
Section: Phalaris Species (Reed Canarygrass)mentioning
confidence: 99%
See 2 more Smart Citations
“…Total indole alkaloid concentration (gramine, tryptamines and carbolines) was inversely correlated with weight gains in lambs and steers (Marten et al 1976). Marten et al (1981) indicated that a total alkaloid concentration greater than 2.0 mg/g dry weight of forage reduces animal gains.…”
Section: Phalaris Species (Reed Canarygrass)mentioning
confidence: 99%
“…These alkaloids are concentrated in the immature leaf sheaths and blades (Woods et al 1979). They reduce palatability of the grass, and thus serve as animal deterrants to prevent overgrazing (Marten et al 1976). The tryptamine and carboline alkaloids create digestive disorders resulting in a greater incidence of diarrhea in sheep compared to either the hordenine or gramine alkaloids (Marten et al 1981).…”
Section: Phalaris Species (Reed Canarygrass)mentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal changes in palatability occur in P. aquatica and P. arundinacea (Oram et al 1985). Genetic variability in palatability has been established for P. arundinacea (Marten et al 1976). In Eragrostis curvula (weeping lovegrass), there are palatability differences between different lines (Leigh 1961;Voight et al 1970) but the reasons are not clear.…”
Section: Plant Characteristics Affecting Voluntary Intakementioning
confidence: 99%
“…Enatic seed yields (Vose 1959) ;Marten 1973;Gander et al 1976). Simons and Marten (19'71) reported highly negative correlations between palatability and total alkaloid content, while Marten et al (1976) In studies on tall fescue (Festuca arundinacea Schreb. ), Bush et al (1970Bush et al ( ,1972 found that pedoline, an alkaloid of this (Coulman et al 1976).…”
mentioning
confidence: 99%